Efficacy and Safety of Tranexamic Acid in Melasma: A Meta-analysis and Systematic Review - Hyun Jung Kim; Seok Hoon Moon; Sang Hyun Cho; Jeong Deuk Lee; Hei Sung Kim (Medical Journals Sweden, 2017)
Tranexamic acid is a novel treatment option for melasma; however, there is no consensus on its use. This systematic review searched major databases for relevant publications to March 2016. Eleven studies with 667 participants were included. Pooled data from tranexamic acid-only observational studies with pre- and post-treatment Melasma Area and Severity Index (MASI) showed a decrease of 1.60 in MASI (95% confidence interval (CI), 1.20-2.00; p < 0.001) after treatment with tranexamic acid. The addition of tranexamic acid to routine treatment modalities resulted in a further decrease in MASI of 0.94 (95% CI 0.10-1.79; p = 0.03). Side-effects were minor, with a few cases reporting hypomenorrhoea, mild abdominal discomfort, and transient skin irritation. These results support the efficacy and safety of tranexamic acid, either alone or as an adjuvant to routine treatment modalities for melasma.